Pengaruh Manajemen Stress dan Kelola Emosi Terhadap Tingkat Kecemasan Siswa di Masa New Normal - Sari, Permata; Bulantika, Siti Zahra; Utami, Ferisa Prasetyaning; Kholidin, Farid Imam (Bulletin of Counseling and Psychotherapy, 2020)
The purpose of this study was to see the effect of stress management and emotional management on students' anxiety levels in the new normal. This research is an ex post facto study using a psychological scale consisting of a student anxiety scale, a stress management scale and a student emotional management scale. The subjects in this study were 120 junior high school students in Central Lampung. The data analysis used is multiple linear regression correlation analysis. The results show that stress management and emotional management have a significant effect on student anxiety in the new normal era. Students' anxiety in the new normal era is related to various factors, namely stress management and emotional management of students.